A Cu-Sb-SnO2 / Ti electrode and preparation method thereof

Through the preparation of Cu-Sb-SnO2/Ti electrodes, the medium and high cost and complex preparation problems of electrochemical water treatment are solved, and high-efficiency and low-energy consumption are achieved. In particular, the rapid removal of tetracycline and stability are improved, which is suitable for large-scale Production and application.

CN115959744BActive Publication Date: 2024-12-31HARBIN INST OF TECH SHENZHEN GRADUATE SCHOOL
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310015738.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-06
Publication Date
2024-12-31
Estimated Expiration
2043-01-06

AI Technical Summary

Technical Problem

In the existing electrochemical water treatment technology, high cost and complex preparation methods limit the industrial production of electrode materials, making it difficult to apply electrode materials on a large scale. The water flow disturbance caused by oxygen evolution side reactions and oxygen production reduces the electrode life and affects pollution. substance degradation efficiency.

Method used

Cu-Sb-SnO2/Ti electrode is prepared by polishing, etching, immersion at room temperature and calcining at Ti substrate to form a Cu and Sb-doped Sn oxide catalytic layer, with appropriate oxygen evolution potential and low charge transfer resistance, improving Electrocatalytic performance and stability.

Benefits of technology

It achieves efficient degradation of tetracycline antibiotic wastewater, reduces the energy consumption of electrochemical water treatment, and the electrode material can completely remove tetracycline within 15 minutes, maintains a 100% removal rate after ten cycles, and is simple and easy to produce on a large scale.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115959744B_ABST
    Figure CN115959744B_ABST
Patent Text Reader

Abstract

The present invention discloses a Cu‑Sb‑SnO2 / Ti electrode and a preparation method thereof, wherein the Cu‑Sb‑SnO2 / Ti electrode comprises a Ti substrate and a catalytic layer disposed on the upper surface of the Ti substrate, wherein the catalytic layer is a Sn oxide doped with Cu and Sb. The present invention has an appropriate oxygen evolution potential, a relatively low charge transfer resistance and excellent electrocatalytic performance, greatly improves the degradation efficiency of antibiotic wastewater simulated by tetracycline, and greatly reduces the operating energy consumption of electrochemical water treatment. The electrode of the present invention can also be extended to the electrochemical oxidation industry to degrade other toxic and harmful pollutants, and can also be used as an anode of electrochemical water treatment technology to degrade antibiotics in water, and has excellent electrochemical performance, efficient antibiotic degradation ability and extremely high stability. The present invention has a simple process, is easy to realize large-scale assembly line production, and is suitable for wide promotion and use.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of electrode material preparation and electrochemical water treatment technology, and in particular relates to a Cu-Sb-SnO2 / Ti electrode and a preparation method of the Cu-Sb-SnO2 / Ti electrode. Background Art

[0002] The rapid development of economy and industry has led to serious water pollution problems. Therefore, there is an urgent need to develop efficient, low-cost and eco-friendly water treatment technologies to ensure the safety of drinking water and the safe discharge of industrial wastewater. Electrochemical water treatment technology is suitable for small decentralized water treatment systems that do not require the addition of chemical reagents. It has the advantages of being green and environmentally friendly and free of secondary pollution. It can provide fast reaction kinetics, modular processing capabilities and simple operation modes. There is a huge demand for this technology in rural areas and industrial plants.

[0003] On the one hand, although commercial electrodes such as Ru / Ir-based DSA electrodes, Pt and BDD exhibit excellent and stable electrocatalytic performance, they cannot be mass-produced and applied due to their high prices. On the other hand, a large number of studies are currently focused on synthesizing "new" electrode materials through methods such as magnetron sputtering, electrodeposition, and hydrothermal reactions, but these preparation methods are limited to laboratory-scale research and are difficult to industrialize. In addition, the preparation cost of complex and novel "new" electrode materials is high and cannot be mass-produced. Therefore, there is an urgent need to develop a low-cost, mass-producible electrode material for use in the field of electrochemical water treatment technology.

[0004] At present, the main challenges faced by the field of electrochemical water treatment technology are: the inevitable oxygen evolution side reaction in the electrochemical oxidation process is not conducive to the production of reactive oxygen. At the same time, the water flow disturbance caused by oxygen production will reduce the life of the electrode. Therefore, the electrode materials used in water treatment technology are required to have appropriate oxygen evolution overpotential, low charge transfer resistance and excellent stability. Summary of the invention

[0005] The first purpose of the present invention is to provide a Cu-Sb-SnO2 / Ti electrode with low cost, simple process and large-scale production. When the Cu-Sb-SnO2 / Ti electrode is used in water treatment technology to degrade pollutants, it has the advantages of high efficiency, high stability and low energy consumption.

[0006] The first object of the present invention is achieved through the following technical measures: a Cu-Sb-SnO2 / Ti electrode, characterized in that it includes a Ti substrate and a catalytic layer arranged on the upper surface of the Ti substrate, and the catalytic layer is Sn oxide doped with Cu and Sb.

[0007] Compared with the traditional Sb-SnO2 electrode, the present invention has a suitable oxygen evolution potential, a lower charge transfer resistance and excellent electrocatalytic performance, greatly improves the degradation efficiency of antibiotic wastewater simulated by tetracycline, and greatly reduces the operating energy consumption of electrochemical water treatment. In addition, the electrode of the present invention can also be extended to the electrochemical oxidation industry to degrade other toxic and harmful pollutants. The present invention can be used as an anode of electrochemical water treatment technology to degrade antibiotics in water, has excellent electrochemical performance, efficient antibiotic degradation ability and extremely high stability, and tetracycline, one of the typical antibiotics, can be completely removed within 15 minutes, and a removal rate of 100% can be achieved after ten cycles of experiments. The present invention has a simple process and is easy to realize large-scale assembly line production, and is suitable for wide promotion and use.

[0008] The second object of the present invention is to provide a method for preparing the above-mentioned Cu-Sb-SnO2 / Ti electrode.

[0009] The second object of the present invention is achieved by the following technical measures: A method for preparing a Cu-Sb-SnO2 / Ti electrode, characterized in that it comprises the following steps:

[0010] S1. Grinding and degreasing the Ti substrate;

[0011] S2, etching the Ti substrate;

[0012] S3, placing the Ti substrate in a precursor solution mixed with Sn, Sb and Cu metal elements for room temperature immersion treatment;

[0013] S4. The Ti substrate after room temperature immersion treatment is subjected to high temperature calcination to obtain a Cu-Sb-SnO2 / Ti electrode.

[0014] In the step S1 of the present invention, the Ti substrate is polished until its surface appears silvery white, and then ultrasonically treated in acetone, ethanol and pure water for 10-15 minutes respectively.

[0015] In the step S1 of the present invention, sandpapers with different mesh sizes are used to polish the Ti substrate in sequence, and the mesh size of the sandpaper used later is greater than the mesh size of the sandpaper used earlier.

[0016] In the step S2 of the present invention, the Ti substrate is subjected to acid etching for 30-50 minutes, and then subjected to ultrasonic treatment in ultrapure water after etching.

[0017] In the step S3 of the present invention, the etched Ti substrate is placed in the precursor solution for 30-60 _ Then slowly take it out vertically and dry it to set.

[0018] The precursor solution of the present invention is prepared by dissolving Cu, Sn and Sb metal salts in an organic solvent. Cu, Sn and Sb metal salts can be metal nitrates, carbonates, etc. Preferably, Cu, Sn and Sb metal inorganic salts are CuCl2, SnCl4 and SbCl3, respectively, and the molar ratio of the three is 0.25-1.5:4:90, and the molar concentrations of the three are specifically 1.25-7.5mM, 20mM, and 450mM. The present invention does not limit the concentration and molar ratio of different metal salts in the precursor solution, and the concentration and molar ratio of the metal salts can be adjusted according to actual conditions.

[0019] In the step S4 of the present invention, the electrode after the room temperature immersion treatment is calcined at high temperature for a first set time:

[0020] (1) If the mass of the catalytic layer loaded on the electrode surface reaches the set value, it is calcined at high temperature for a second set time, and then the surface is washed with deionized water and dried to obtain a Cu-Sb-SnO2 / Ti electrode.

[0021] ⑵If the mass of the catalytic layer loaded on the electrode surface does not reach the set value, proceed to step S3, until the mass of the catalytic layer loaded on the electrode surface after high-temperature calcination reaches the set value, proceed to step ⑴.

[0022] The mass setting value of the catalyst layer loaded on the electrode surface of the present invention is 0.5-3.0 mg / cm 2 .

[0023] In the step S4 of the present invention, the high temperature calcination is carried out in a muffle furnace at 450-650°C.

[0024] Compared with the prior art, the present invention has the following significant effects:

[0025] ⑴ Compared with the traditional Sb-SnO2 electrode, the present invention has a suitable oxygen evolution potential, a lower charge transfer resistance and excellent electrocatalytic performance, which greatly improves the degradation efficiency of tetracycline-simulated antibiotic wastewater and greatly reduces the operating energy consumption of electrochemical water treatment.

[0026] (2) The electrode of the present invention can also be extended to the electrochemical oxidation industry to degrade other toxic and harmful pollutants.

[0027] ⑶ The present invention can be used as an anode for electrochemical water treatment technology to degrade antibiotics in water. It has excellent electrochemical performance, efficient antibiotic degradation ability and extremely high stability. Tetracycline, one of the typical antibiotics, can be completely removed within 15 minutes, and a removal rate of 100% can be achieved after ten cycles of experiments.

[0028] (4) The process of the present invention is simple, and can be easily realized in large-scale assembly line production, and is suitable for wide promotion and use. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments.

[0030] Figure 1 It is a linear sweep voltammetric curve of the Cu-Sb-SnO2 / Ti electrode prepared by the present invention;

[0031] Figure 2 It is the electrochemical impedance spectrum of the Cu-Sb-SnO2 / Ti electrode prepared by the present invention;

[0032] Figure 3 is a chart showing the degradation effects of different electrode materials prepared by the present invention on tetracycline;

[0033] Figure 4 is a graph showing the degradation effect of the Cu-Sb-SnO2 / Ti electrode prepared by the present invention using different Cu ratios on tetracycline;

[0034] Figure 5 It is a chart showing the cycle test results of the degradation of tetracycline by the Cu-Sb-SnO2 / Ti electrode of the present invention.

[0035] Figure 6 This is a chart of ion dissolution during the cycle experiment of tetracycline degradation by the Cu-Sb-SnO2 / Ti electrode of the present invention. DETAILED DESCRIPTION

[0036] In order to more clearly understand the above-mentioned objectives, features and advantages of the present disclosure, the scheme of the present disclosure will be further described below. It should be noted that the embodiments of the present disclosure and the features in the embodiments can be combined with each other without conflict.

[0037] In the following description, many specific details are set forth to facilitate a full understanding of the present disclosure, but the present disclosure may also be implemented in other ways different from those described herein; it is obvious that the embodiments in the specification are only part of the embodiments of the present disclosure, rather than all of the embodiments.

[0038] The preferred embodiments of the present invention will be described in detail below in conjunction with examples. It should be understood that the following examples are provided only for the purpose of illustration and are not intended to limit the scope of the present invention. Those skilled in the art may make various modifications and substitutions to the present invention without departing from the purpose and spirit of the present invention.

[0039] The present invention is described below by means of specific embodiments, but the present invention is not limited thereto.

[0040] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.

[0041] Example 1

[0042] The invention discloses a Cu-Sb-SnO2 / Ti electrode, which comprises a Ti substrate and a catalyst layer arranged on the upper surface of the Ti substrate, wherein the catalyst layer is Sn oxide doped with Cu and Sb.

[0043] A method for preparing the above-mentioned Cu-Sb-SnO2 / Ti electrode comprises the following steps:

[0044] S1. Grinding and degreasing the Ti substrate;

[0045] Specifically, the Ti substrate was polished with sandpaper (first with 800 mesh, then with 1200 mesh) to make the surface appear silvery white, and then ultrasonically treated in acetone, ethanol, and pure water for 10-15 min respectively.

[0046] S2, etching the Ti substrate;

[0047] Specifically, the Ti substrate is treated with 10wt% oxalic acid at 98°C for 30-50 minutes, and then ultrasonicated in ultrapure water for 5 minutes for standby use.

[0048] S3, placing the Ti substrate in a precursor solution mixed with Sn, Sb and Cu metal elements for room temperature immersion treatment;

[0049] Specifically, the Ti substrate is placed in the prepared precursor solution for 30-60 seconds, then slowly taken out vertically and placed in an oven at 85°C for drying and shaping for 5 minutes.

[0050] The precursor solution is prepared by dissolving CuCl2, SnCl4 and SbCl3 in isopropanol, and the molar ratio of CuCl2, SnCl4 and SbCl3 is 0.25-1.5:4:90, specifically 1.25-7.5mM, 20mM and 450mM respectively.

[0051] S4, calcining the electrode after room temperature immersion treatment at high temperature for a first set time:

[0052] (1) If the mass of the catalytic layer loaded on the electrode surface reaches the set value, it is calcined at high temperature for a second set time, and then the surface is washed with deionized water and dried to obtain a Cu-Sb-SnO2 / Ti electrode.

[0053] ⑵If the mass of the catalytic layer loaded on the electrode surface does not reach the set value, proceed to step S3, until the mass of the catalytic layer loaded on the electrode surface after high-temperature calcination reaches the set value, proceed to step ⑴.

[0054] The catalyst layer mass setting value loaded on the electrode surface is 0.5-3.0 mg / cm 2 .

[0055] Specifically, the electrode after room temperature immersion treatment is placed in a muffle furnace at 550°C and calcined for a first set time of 10 minutes, and then transferred to step S3 until the mass of the catalyst layer loaded on the electrode surface reaches 2.0 mg / cm 2 The electrode reaching the mass load was calcined in a muffle furnace at 550° C. for a second set time of 60 min, taken out, and the surface was washed with deionized water and dried to obtain a Cu-Sb-SnO2 / Ti electrode.

[0056] Comparative Example 1

[0057] The preparation method of the Ti / Sb-SnO2 electrode is different from that of Example 1 in that the precursor solution is prepared differently. The precursor solution is composed of SnCl4 and SbCl3 in a molar ratio of 4:90, specifically 20 mM and 450 mM, respectively.

[0058] Example 2

[0059] In order to further illustrate that the present invention obtains an electrode material with excellent electrocatalytic performance, the electrochemical performance of the obtained product was characterized, including linear sweep voltammetry (LSV) and electrochemical impedance spectroscopy (EIS).

[0060] The test conditions are as follows: a three-electrode system consisting of a Chenhua 660E electrochemical workstation, Ag / AgCl as the reference electrode, the prepared electrode material as the working electrode, and a Pt electrode as the counter electrode; the electrolyte is 50 mM Na2SO4 solution, the LSV scan rate is 10 mV / s, and the EIS frequency is 0.01-10 6 Hz, with an amplitude of 10mV.

[0061] Figure 1 Yes and Figure 2 The LSV and EIS characterization results of the prepared electrodes are shown in Figure 2. It can be seen that the prepared Cu-Sb-SnO2 / Ti electrode has a suitable oxygen evolution potential (2.86V vs. RHE) and a lower charge transfer resistance (2.5Ω) compared with the traditional Sb-SnO2 electrode, which is conducive to the generation of active oxygen.

[0062] Example 3

[0063] In order to verify the prospect of applying the electrode prepared in the present invention to electrochemical water treatment technology, the electrode material prepared in Example 1 was used as an anode to carry out an antibiotic degradation experiment.

[0064] The test conditions are as follows: the anode is the Cu-Sb-SnO2 / Ti electrode prepared in Example 1 and the Ti / Sb-SnO2 / Ti electrode prepared in Comparative Example 1. 2 The electrode and cathode are inert graphite electrodes; the electrolyte is 50 mM Na 2 SO 4 Solution, electrode spacing 1cm. Anode effective area 4cm 2 , the cathode effective area is 1cm 2 ; Tetracycline concentration is 10 mg / L; current density is 10 mA / cm 2 .

[0065] Figure 3 The degradation effect of different electrode materials on tetracycline. The results show that compared with the Ti / Sb-SnO2 electrode prepared in Comparative Example 1, the degradation efficiency of the Cu-Sb-SnO2 / Ti electrode prepared in Example 1 is greatly improved, and the Cu-Sb-SnO2 / Ti electrode can completely remove tetracycline in 15 minutes.

[0066] Example 4

[0067] The degradation effect of the Cu-Sb-SnO2 / Ti electrode with different Cu ratios prepared in Example 1 on tetracycline was tested. Except for the different electrode materials of the anode, other test conditions were the same as in Example 3. The anode material used was the Cu-Sb-SnO2 / Ti electrode with different Cu ratios prepared in Example 1.

[0068] Figure 4 The degradation effect of Cu-Sb-SnO2 / Ti electrodes prepared with different Cu ratios on tetracycline. The results show that the electrode materials prepared with different Cu ratios have excellent electrocatalytic performance, and the requirements for the ratio of the precursor solution during the preparation process are relatively loose, which is more advantageous for industrial production.

[0069] Example 5

[0070] In order to verify the stability of the electrode material prepared by the present invention, a cycle experiment of antibiotic degradation and detection of electrode metal ion dissolution were carried out under the conditions of Example 3.

[0071] Figure 5 The results of the cyclic experiment of tetracycline degradation by Cu-Sb-SnO2 / Ti electrode show that the electrode material prepared by the present invention is very stable and still maintains the initial electrocatalytic performance after 10 degradation cycles. Figure 6The ion dissolution results showed that the dissolution of Cu, Sn and Sb ions was extremely low, only <15 μg / L, even meeting the drinking water standard.

[0072] Example 6

[0073] The energy consumption of tetracycline degradation by the electrode materials prepared in Example 1 was compared. Compared with the traditional Ti / Sb-SnO2 electrode (0.287 kWh / g), the Cu-Sb-SnO2 / Ti electrode has extremely low operating energy consumption (0.0388 kWh / g).

[0074] The above description is only a specific embodiment of the present disclosure, so that those skilled in the art can understand or implement the present disclosure. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present disclosure. Therefore, the present disclosure will not be limited to the embodiments described herein, but will conform to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a Cu-Sb-SnO2 / Ti electrode, the Cu-Sb-SnO2 / Ti electrode comprising a Ti substrate and a catalyst layer disposed on the upper surface of the Ti substrate, wherein the catalyst layer is a Sn oxide doped with Cu and Sb, characterized in that: The preparation method comprises the following steps: S1. Grinding and degreasing the Ti substrate; S2, etching the Ti substrate; S3, placing the Ti substrate in a precursor solution mixed with Sn, Sb and Cu metal elements for room temperature immersion treatment; the precursor solution is CuCl2, SnCl4, SbCl3 dissolved in an organic solvent, and the molar ratio of CuCl2, SnCl4, SbCl3 is 0.25-1.5:4:90; S4, calcining the Ti substrate after the room temperature immersion treatment at high temperature. In the step S4, the electrode after the room temperature immersion treatment is calcined at high temperature for a first set time: (1) If the mass of the catalyst layer loaded on the electrode surface reaches the set value, calcination is performed at high temperature for a second set time, and then the surface is washed with deionized water and dried to obtain a Cu-Sb-SnO2 / Ti electrode; (2) If the mass of the catalyst layer loaded on the electrode surface does not reach the set value, proceed to step S3, until the mass of the catalyst layer loaded on the electrode surface after high-temperature calcination reaches the set value, proceed to step (1); The mass setting value of the catalyst layer loaded on the electrode surface is 0.5-3.0 mg / cm 2 .

2. The preparation method according to claim 1, characterized in that: In the step S1, the Ti substrate is polished until its surface appears silvery white, and then ultrasonically treated in acetone, ethanol and pure water for 10-15 minutes respectively.

3. The preparation method according to claim 2, characterized in that: In the step S1, sandpapers with different mesh sizes are used to polish the Ti substrate, and the mesh size of the sandpaper used later is greater than the mesh size of the sandpaper used earlier.

4. The preparation method according to claim 3, characterized in that: In the step S2, the Ti substrate is subjected to acid etching for 30-50 minutes, and then subjected to ultrasonic treatment in ultrapure water.

5. The preparation method according to claim 4, characterized in that: In the step S3, the etched Ti substrate is placed in the precursor solution for 30-60 seconds, then slowly taken out vertically and dried to fix the shape.

6. The preparation method according to claim 5, characterized in that: In step S4, high temperature calcination is performed in a muffle furnace at 450-650°C.